2002
DOI: 10.1074/jbc.m200221200
|View full text |Cite
|
Sign up to set email alerts
|

Charcot-Leyden Crystal Protein (Galectin-10) Is Not a Dual Function Galectin with Lysophospholipase Activity but Binds a Lysophospholipase Inhibitor in a Novel Structural Fashion

Abstract: Charcot-Leyden crystal (CLC) protein, initially reported to possess weak lysophospholipase activity, is still considered to be the eosinophil's lysophospholipase, but it shows no sequence similarities to any known lysophospholipases. In contrast, CLC protein has moderate sequence similarity, conserved genomic organization, and near structural identity to members of the galectin superfamily, and it has been designated galectin-10. To definitively determine whether or not CLC protein is a lysophospholipase, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 56 publications
1
113
0
Order By: Relevance
“…Gal-10 was found to be essential for the functional properties of CD25(+) Treg cells. 57,58 Gal-12 is preferentially expressed in peripheral blood leukocytes and adipocytes. Previously, it was shown that Gal-12 is induced by cell cycle block at the G(1) phase and causes G(1) arrest when overexpressed.…”
Section: Role Of Galectins In Trophoblast Invasionmentioning
confidence: 99%
“…Gal-10 was found to be essential for the functional properties of CD25(+) Treg cells. 57,58 Gal-12 is preferentially expressed in peripheral blood leukocytes and adipocytes. Previously, it was shown that Gal-12 is induced by cell cycle block at the G(1) phase and causes G(1) arrest when overexpressed.…”
Section: Role Of Galectins In Trophoblast Invasionmentioning
confidence: 99%
“…In addition to the galactosyltransferase domain, all members of subfamily 1 contain a putative galactoside binding lectin domain with similarity to human galectins (Ackerman et al, 2002). Interestingly, such a lectin domain is not present in mammalian B3GALTs (Hennet, 2002).…”
Section: Online)mentioning
confidence: 99%
“…LGALS-14 is thought to be the homologue of human galectin-10, which is also secreted by eosinophils (Ackerman et al 2002). Analysis of H. contortus infected sheep demonstrated release of LGALS-14 into the gastrointestinal mucus, the interface of host and parasite interaction (Dunphy et al 2002).…”
Section: Ietroductioementioning
confidence: 99%